QSAR-analysis of 1-[2-(R-phenylimino)-4-methyl-3-(3-[morpholine-4-yl]propyl)-2,3-dihydro-1,3-thiazol-5-yl]ethane-1-one's derivatives as potential antioxidants - Іryna Drapak; Borys Zimenkovsky; Lina Perekhoda; Hanna Yeromina; Kateryna Lipakova; Inna Demchuk; Marina Rakhimova (Pensoft Publishers, 2019)
Aim. The aim of study was to determine of the parameters of the molecular structure of new 1-[2-(R-phenylimino)-4-methyl-3-(3-[morpholine-4-yl]propyl)-2,3-dihydro-1,3-thiazol-5-yl]ethane-1-one derivatives and QSAR-analysis. The latter can be considered as the theoretical basis for de novo design of new potential antioxidants. Materials and methods. 14 new derivatives of 1-[2-(R-phenylimino)-4-methyl-3-(3-[morpholine-4-yl] propyl)-2,3-dihydro-1,3-thiazol-5-yl]ethane-1-one were involved in the study and their antioxidant activities were evaluated. Hyper-Chem 7.59 and BuildQSAR software were used for calculation of molecular descriptors and building the QSAR-models. Results. The calculation of number of molecular descriptors (electronic, steric, geometric, energy) was carried out for the tested compounds: 14 derivatives of 1-[2-(R-phenylimino)-4-methyl-3-(3-[morpholine-4-yl] propyl) -2,3-dihydro-1,3-thiazol-5-yl]ethane-1-one. For QSAR analysis, the compounds studied were divided into a training and test sample. The correlations between the antioxidant activity level and abovementioned molecular descriptors were shown in multivariate linear QSAR-model: Activity = ∑хіаі + bі, where xi - molecular descriptor. Based on the analysis of the obtained QSAR-models, it was found that antioxidant activity increases with decreasing of the area, molecular volume, lipophilicity, polarisation and increasing the magnitude of the dipole moment. The increase in the energy of the bonds, the energy of inter-nuclear interactions, the energy of the lower vacant molecular orbit and the reduction of the energy of hydration and energy of the higher vacant molecular orbitals also results in an increase in the antioxidant activity. The greatest effect of effective charges on atoms on the antioxidant activity was detected: the increase in the charge value on the morpholine cycle Oxygen and the decrease in the charge size on the Sulphur atom of the thiazole ring and the Oxygen atom of the acetyl group. QSAR models with better statistics were selected. QSAR models obtained are characterised by high predictive ability, determined both by internal and external validation and can be used for virtual screening of the antioxidant activity of substances of this class of compounds. Conclusions. 1). The study of the structure-activity relationships for 1-[2-(R-phenylimino)-4-methyl-3-(3- [morpholine-4-yl]propyl)-2,3-dihydro-1,3-thiazol-5-yl]ethane-1-one derivatives were carried out. 2). QSAR analysis revealed the following: polarisation, dipole moment, lipophilicity, energy parameters as well as the size of the molecule and its branching possessed the most significant effect on antioxidant activity; the antioxidant activities of the compounds were increased with the increase in their hydrophilic and reductive properties; the molecules with small volume and surface area showed the higher level of antioxidant activity. 3). Obtained QSAR models are proposed for antioxidant activity prediction within the above-mentioned row of compounds and can be considered as a theoretical basis for de novo design of new potential antioxidants.